2022
DOI: 10.1088/2053-1591/ac565e
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar resistive switching in Ag/VO2(B)/SiOx/n++Si RRAM

Abstract: Non-volatile resistive random-access memory (RRAM) is being promoted as a possible alternative to flash memory, however the optimal material system and sophisticated fabrication techniques hinder its utilization in practical routes. Here, we demonstrate the direct fabrication of metal/oxides/semiconductor (MOS) structured Ag/VO2(B)/SiOx/n++Si RRAM via drop-coating process, in which bipolar resistive switching behavior was obtained and investigated systematically. The RRAM devices exhibit good cycle-to-cycle en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The properties of the CBRAM device with the VO x layer are summarized and compared with previously reported devices in Table . ,, Compared with other reports on vanadium oxide–based CBRAM devices, our device shows advanced or comparable performance with a low operation voltage, a low programming time, a high on/off ratio, good cycling endurance, and good retention properties.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…The properties of the CBRAM device with the VO x layer are summarized and compared with previously reported devices in Table . ,, Compared with other reports on vanadium oxide–based CBRAM devices, our device shows advanced or comparable performance with a low operation voltage, a low programming time, a high on/off ratio, good cycling endurance, and good retention properties.…”
Section: Resultsmentioning
confidence: 83%
“…24 The resistive switching in Ag/VO 2 /SiO x /n ++ -Si devices using brookite-phase vanadium dioxide nanorods occurs at voltages of +3 V and −3 V for SET and RESET, respectively. 26 In addition, Yalagala et al reported that the switching in vanadium oxide nanosheet-based flexible memristors with an Ag/V 2 O 5 /Cu structure occurs at V SET and V RESET of approximately ±1 V, respectively. 27 As aforementioned, the facilitated switching in CBRAM devices requires a high migration rate of metal cations in oxides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation